Depression and anxiety among people with hypertension on follow-up in Eastern Ethiopia: A multi-center cross-sectional study - Abdisa, Lemesa; Letta, Shiferaw; Nigussie, Kabtamu (Frontiers in Psychiatry, 2022)
AAbstract Background: Even though depressive and anxiety symptoms are common among hypertensive patients, there is a paucity of data regarding comorbid depression and anxiety symptoms in Ethiopia. Objective: the aim of this study was to determine the magnitude and associated factors of depression, anxiety symptoms among hypertensive patients on follow-up at public hospitals, in eastern Ethiopia. Method: An institutional-based cross-sectional study was conducted on 491 hypertensive patients at four public hospitals in Harar and Dire Dawa Administration. Participants were randomly selected using a systematic random sampling technique. Data was collected by interviewer-administered structured questionnaires. A validated nine-items Patient Health Questionnaire (PHQ-9) and Generalized Anxiety Disorder scales were used to assess depression and anxiety symptoms respectively. Logistic regression analyses were employed to identify variables associated with comorbid depression and anxiety, and it was reported using adjusted odds ratio along with 95% confidence interval (CI). A variable with P-values < 0.05 in the adjusted analysis was a cut-off point for the statistically significant association. Results: Out of 471 participants included in the study, 27.2%, 32.7% had depression and anxiety symptoms respectively. Being female (AOR=1.74, 1.09-2.78), no formal education (AOR=2.19, 1.19-4.81), comorbid medical illness (AOR= 2.23, 1.39-3.56), family history of depression (AOR= 2.01, 1.25-3.19), and poor social support (AOR=2.80, 1.60-5.22) were statistically associated with depressive symptoms. While being females (AOR=1.54, 1.01-2.35), being widowed/divorced (AOR=2.22, 1.41-3.52), having a comorbid medical illness (AOR=1.64, 1.06-2.53) and poor social support (AOR= 3.54, 2.09-6.01) were statistically associated with anxiety symptoms at a p-value < 0.05. Conclusion: The findings of the current study showed that the magnitudes of depressive and anxiety symptoms in patients with hypertension were relatively high. Being female, comorbid other medical illnesses, and poor social support were statistically associated with both depression and anxiety. Regular screening, early identification, diagnosis and providing appropriate intervention for depression and anxiety in hypertensive patients need to be a great concern for the health care providers.